2016
DOI: 10.1089/thy.2015.0657
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal System Obstruction After Radioiodine Therapy in Differentiated Thyroid Carcinomas: A Prospective Comparative Study

Abstract: In this study, an active prospective investigation allowed LSO detection during the first six months after RIT. This finding demonstrates the importance of making this association clear to patients and health professionals, with a view to early diagnosis, appropriate treatment, and preventing LSO-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
0
10
1
12
Order By: Relevance
“…Studies of diseased state microbiota have been conducted in patients with dry eyes ( Willis et al, 2020 ; Andersson et al, 2021 ), obstruction ( Curragh et al, 2020 ), and Sjogren’s syndrome ( Trujillo-Vargas et al, 2020 ). Although dry eyes are a known side effect of radiotherapy ( Nuzzi et al, 2020 ) and radioiodine treatments ( da Fonseca et al, 2016 ), research in the area of radiation impact on the lacrimal or ocular microbiota has yet to be conducted.…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%
“…Studies of diseased state microbiota have been conducted in patients with dry eyes ( Willis et al, 2020 ; Andersson et al, 2021 ), obstruction ( Curragh et al, 2020 ), and Sjogren’s syndrome ( Trujillo-Vargas et al, 2020 ). Although dry eyes are a known side effect of radiotherapy ( Nuzzi et al, 2020 ) and radioiodine treatments ( da Fonseca et al, 2016 ), research in the area of radiation impact on the lacrimal or ocular microbiota has yet to be conducted.…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%
“…Nasolacrimal duct obstruction has been associated with high-dose radioiodine therapy (Kloos et al 2002, Ali 2016, da Fonseca et al 2016. Morgenstern et al (2005) showed that NIS mRNA was detected in normal lacrimal sacs via RT-PCR and NIS immunostaining was detected at the basolateral membrane of the stratified columnar epithelial cells in the lacrimal sac (Fig.…”
Section: Nis Expression In Lacrimal Sac and Nasolacrimal Ductmentioning
confidence: 99%
“… 1 Epiphora and nasolacrimal duct obstruction have also been reported as adverse effects. 3 , 4 Da Fonseca et al 5 conducted a prospective study to evaluate the effect of iodine-131 on the lacrimal drainage system. They reported that the rate of lacrimal system obstruction is 6.8% until 12 months after RAI.…”
Section: Introductionmentioning
confidence: 99%